Electromagnetic and Mechanical Characteristics Analysis of a Flat-Type Vertical-Gap Passive Magnetic Levitation Vibration Isolator - Baoquan Kou; Yiheng Zhou; Xiaobao Yang; Feng Xing; He Zhang (Shock and Vibration)
In this paper, we describe a flat-type vertical-gap passive magnetic levitation vibration isolator (FVPMLVI) for active vibration isolation system (AVIS). A dual-stator scheme and a special stator magnet array are adopted in the proposed FVPMLVI, which has the effect of decreasing its natural frequency, and this enhances the vibration isolation capability of the FVPMLVI. The structure, operating principle, analytical model, and electromagnetic and mechanical characteristics of the FVPMLVI are investigated. The relationship between the force characteristics (levitation force, horizontal force, force ripple, and force density) and major structural parameters (width and thickness of stator and mover magnets) is analyzed by finite element method. The experiment result is in good agreement with the theoretical analysis.